Noterelle al «Filostrato» e al «Ninfale fiesolano» di Giovanni Boccaccio (Carte Romanze, 2022)
Abstract: This paper presents three brief reading notes on as many passages of the Filostrato (IV 51:1-8; IV 56, 4-8) and the Ninfale fiesolano (229, 1-5) by Giovanni Boccaccio, in the search for probable classical and medieval latin sources and models that have so far escaped the attention of scholars.